2008
DOI: 10.1111/j.1365-2672.2008.03824.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and antifungal evaluation of a food-grade U-type microemulsion

Abstract: Aims:  Food‐grade microemulsions have been of increasing interest to researchers as potential delivery systems for bioactive compounds. However, food‐grade microemulsions are difficult to formulate and no microemulsion has been documented for antifungal purpose. The physicochemical characterization of a food‐grade glycerol monolaurate (GML)/ethanol (EtOH)/Tween 80/potassium sorbate (PS)/water microemulsion system and the antifungal activities against Aspergillus niger and Penicillium italicum have been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Similar results were also published by Zhang et al [25], Mansour et al [27] and Altieri et al [28]. They found out that effect of fatty acids and MAG against micromycetes growth is specific for individual strains or species.…”
Section: Antifungal Activity Of Micromycetes On Culture Mediasupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were also published by Zhang et al [25], Mansour et al [27] and Altieri et al [28]. They found out that effect of fatty acids and MAG against micromycetes growth is specific for individual strains or species.…”
Section: Antifungal Activity Of Micromycetes On Culture Mediasupporting
confidence: 86%
“…Inhibition of growth of this species was observed using 164 mg/L monolaurin and spore inhibition using 300 mg/L monolaurin. According Zhang et al [25,26] microemulsions containing monolaurin can modify the morphology of A. niger. The microemulsions inhibited growth and conidiation both of aspergilli and penicillia.…”
Section: Antifungal Activity Of Micromycetes On Culture Mediamentioning
confidence: 98%
“…Our previous GML-loaded microemulsion with solubilization of potassium sorbate showed 80% A. niger growth inhibition at 0.2% and 72% P. italicum growth inhibition at 0.1%, and a delay of conidiation of 2 days compared with the control (Zhang et al, 2008a). The GML- loaded microemulsion prepared by Fu et al (2006) inhibited 78% A. niger growth at 0.05% after 5 days of incubation.…”
Section: Discussionmentioning
confidence: 87%
“…Sodium diacetate (SD), the sodium salt of the acetic acid, is an economical GRAS ingredient by the US FDA (Shelef and Addala, 1994). Our previous work (Zhang et al, 2008a) showed that the solubilization of water-soluble salts with antimicrobial properties in microemulsions could enhance the antimicrobial effects.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has studied food‐grade microemulsions stabilized by short‐chain alcohols for antimicrobial purpose (Zhang et al . 2008a,b).…”
Section: Introductionmentioning
confidence: 99%